Enhanced Acid Sensitivity of Pressure-Damaged Escherichia coli O157 Cells - Pagán, Rafael (American Society for Microbiology, 2001)
Pressure-damaged Escherichia coli O157 cells were more acid sensitive than native cells and were impaired in pH homeostasis. However differences in acid sensitivity were not related to differences in cytoplasmic pH (pH(i)). Cellular β-galactosidase was more acid labile in damaged cells. Sensitization to acid may thus involve loss of protective or repair functions.